2018
DOI: 10.1111/1745-5871.12284
|View full text |Cite
|
Sign up to set email alerts
|

Concerning values: what underlies public polarisation about climate change?

Abstract: Climate change is a partisan issue, with increasingly politically polarised responses, particularly in Anglophone countries. While politics clearly have a role in determining attitudes to climate science and policy, understanding the human values that underlie attitudes offers advantages over a focus on political differences. This study examines public concern about climate change in Hobart, the state capital of Tasmania, Australia. Hobart is a microcosm of polarisation about environmental issues due to its lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 69 publications
1
29
0
Order By: Relevance
“…Localized effects of climate change are complex, and adaptation action is often the subject of political disagreement, so reliance on private interests may not lead to fair or legitimate outcomes (Adger, Barnett, Brown, Marshall, & O'Brien, 2012). Risk‐reflective pricing is limited in its effectiveness as an incentive to adapt because social values, rather than economic values, are more likely to affect people's willingness to act on climate change (Evans et al, 2012; Lucas, 2018). Without reference to social values and context, technocratic forms of risk measurement and calculation make trade‐offs based on limited information.…”
Section: Resultsmentioning
confidence: 99%
“…Localized effects of climate change are complex, and adaptation action is often the subject of political disagreement, so reliance on private interests may not lead to fair or legitimate outcomes (Adger, Barnett, Brown, Marshall, & O'Brien, 2012). Risk‐reflective pricing is limited in its effectiveness as an incentive to adapt because social values, rather than economic values, are more likely to affect people's willingness to act on climate change (Evans et al, 2012; Lucas, 2018). Without reference to social values and context, technocratic forms of risk measurement and calculation make trade‐offs based on limited information.…”
Section: Resultsmentioning
confidence: 99%
“…Several other papers have also found that women show more environmental or climate change concern (Aasen, ; Blocker & Eckberg, ; Gifford & Nilsson, ; Hamilton, ; McCright, Dunlap, & Marquart‐Pyatt, ; Melgar, Mussio, & Rossi, ; Olofsson & Öhman, ; Torgler, Garcia‐Valiñas, & Macintyre, ), others have found no impact of gender (Bodur & Sarigöllü, ; Gelissen, ; Lucas, ; Mostafa, ), but Abdul‐Wahab and Abdo () found that women show lower environmental concern than men in Oman. Moreover, Knight (), focusing on the gender difference in CCC among different countries, found that women show more concern than men in wealthier countries, but the reverse is observed in poorer countries.…”
Section: Theoretical and Empirical Framework And Hypothesesmentioning
confidence: 99%
“…Alternatively, more education can be associated with higher income that consequently allows individuals to pay more attention to the environment and less to personal economic issues (Gelissen, ). Interestingly, Lucas () finds no effect of education on CCC, and Mostafa () finds that education has a negative effect on pro‐environmental intentions.…”
Section: Theoretical and Empirical Framework And Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…The promise and delivery of improved quality of life with social participation [9], and the role of Smart Systems in creating more efficient, effective [10], and more sustainability and leisure or health-oriented societies [11][12][13] is evident. The use and/or distribution of resources (e.g., water), whether politically motivated or otherwise [14,15] as related to policy, are also laudable. Further, the combination of real-time in situ observational platforms [16] that include immediate dissemination offer the public access to view and monitor events or situations of interest continuously.…”
Section: Introductionmentioning
confidence: 99%